Sonic hedgehog Promotes G(1) Cyclin Expression and Sustained Cell Cycle Progression in Mammalian Neuronal Precursors - Kenney, Anna Marie (American Society for Microbiology, 2000)
Sonic hedgehog (Shh) signal transduction via the G-protein-coupled receptor, Smoothened, is required for proliferation of cerebellar granule neuron precursors (CGNPs) during development. Activating mutations in the Hedgehog pathway are also implicated in basal cell carcinoma and medulloblastoma, a tumor of the cerebellum in humans. However, Shh signaling interactions with cell cycle regulatory components in neural precursors are poorly understood, in part because appropriate immortalized cell lines are not available. We have utilized primary cultures from neonatal mouse cerebella in order to determine (i) whether Shh initiates or maintains cell cycle progression in CGNPs, (ii) if G(1) regulation by Shh resembles that of classical mitogens, and (iii) whether individual D-type cyclins are essential components of Shh proliferative signaling in CGNPs. Our results indicate that Shh can drive continued cycling in immature, proliferating CGNPs. Shh treatment resulted in sustained activity of the G(1) cyclin-Rb axis by regulating levels of cyclinD1, cyclinD2, and cyclinE mRNA transcripts and proteins. Analysis of CGNPs from cyclinD1(−/−) or cyclinD2(−/−) mice demonstrates that the Shh proliferative pathway does not require unique functions of cyclinD1 or cyclinD2 and that D-type cyclins overlap functionally in this regard. In contrast to many known mitogenic pathways, we show that Shh proliferative signaling is mitogen-activated protein kinase independent. Furthermore, protein synthesis is required for early effects on cyclin gene expression. Together, our results suggest that Shh proliferative signaling promotes synthesis of regulatory factor intermediates that upregulate or maintain cyclin gene expression and activity of the G(1) cyclin-Rb axis in proliferating granule neuron precursors.